Atmospheric conditions associated with extreme fire activity in the Western Mediterranean region - Amraoui, Malik; Pereira, Mário G.; DaCamara, Carlos C.; Calado, Teresa J. (The Science of the total environment, 2015)
Active fire information provided by TERRA and AQUA instruments on-board sun-synchronous polar MODIS platform is used to describe fire activity in the Western Mediterranean and to identify and characterize the synoptic patterns of several meteorological fields associated with the occurrence of extreme fire activity episodes (EEs). The spatial distribution of the fire pixels during the period of 2003–2012 leads to the identification of two most affected sub-regions, namely the Northern and Western parts of the Iberian Peninsula (NWIP) and Northern Africa (NAFR). The temporal distribution of the fire pixels in these two sub-regions is characterized by: (i) high and non-concurrent inter- and intra-annual variability with maximum values during the summer of 2003 and 2005 in NWIP and 2007 and 2012 in NAFR; and, (ii) high intra-annual variability dominated by a prominent annual cycle with a main peak centred in August in both sub-regions and a less pronounced secondary peak in March only evident in NWIP region. The 34 EEs identified were grouped according to the location, period of occurrence and spatial configuration of the associated synoptic patterns into 3 clusters (NWIP-summer, NWIP-winter and NAFR-summer). Results from the composite analysis reveal similar fire weather conditions (statistically significant positive anomalies of air temperature and negative anomalies of air relative humidity) but associated with different circulation patterns at lower and mid-levels of the atmosphere associated with the occurrence of EEs in each cluster of the Western Mediterranean region. •West Iberia (WI) and North Africa are the sub-regions most affected by fires.•Fire annual cycle has a main peak in August and secondary peak in March over WI.•Extreme fire activity episodes are identified in both summer and winter seasons.•Extreme fire episodes occur in 5% of days but represent 22% of total fire pixels.•Fire occurs under similar weather conditions but different circulation patterns.